Use of analgesics (opioids and nonsteroidal anti-inflammatory drugs) and dementia related neuropathology in a community-based autopsy cohort - Dublin, Sascha (J Alzheimers Dis, 2017)
BACKGROUND: Opioids may influence the development of Alzheimer’s Disease (AD). Some studies have observed AD pathology in the brains of opioid abusers. No study has examined the association between prescription opioid use and dementia-related neuropathologic changes. OBJECTIVE: To examine the relationship between prescription opioid or NSAID use and dementia-related neuropathologic changes. METHODS: Within a community-based autopsy cohort (N=420), we ascertained opioid and nonsteroidal anti-inflammatory drug (NSAID) use over a 10 year period from automated pharmacy data and calculated total standardized daily doses (TSDDs). A neuropathologist assessed outcomes including neuritic plaques, neurofibrillary tangles, and macroscopic infarcts. Outcome measures were dichotomized using established cutpoints. We used modified Poisson regression to calculate adjusted relative risks (RR) and 95% confidence intervals (CI), accounting for participant characteristics and using weighting to account for possible selection bias related to selection into the autopsy sample. RESULTS: Heavier opioid exposure was not associated with greater neuropathologic changes. For neuritic plaques, the adjusted RR [95% CI] was 0.99 [0.64–1.47] for 91+ TSDDs of opioids vs. little to no use, and for neurofibrillary tangles, 0.97 [0.49–1.78]. People with heavy NSAID use had higher risk of neuritic plaques (RR 1.39 [1.01–1.89]) than those with little to no use, as we have previously reported. Neither opioid nor NSAID use was associated with higher risk of macroscopic infarcts or with Lewy body disease. CONCLUSION: Prescription opioid use is not associated with dementia-related neuropathologic changes, but heavy NSAID use may be. More research is needed examining chronic pain, its pharmacologic treatments and neuropathologic changes.